Writing Out of Place: Wordsworth and Woolf in London - Laurent Folliot; Juliana Lopoukhine (Sillages Critiques)
The present article endeavours to shed light on some unlikely yet deep-seated affinities between William Wordsworth and Virginia Woolf, in particular on their common love of roaming. Although Wordsworth’s country rambles have often been associated with the kind of patriarchal culture epitomised by Woolf’s father Leslie Stephen (who even penned an essay entitled “In Praise of Walking”), the London perambulations recounted in Book VII of The Prelude present suggestive analogies, as well as contrasts, with Woolf’s Modernist city heuristics. Both were, in a sense, outsiders to the metropolitan space they negotiated in writing, and both were keenly aware of living through a moment of historical crisis and opportunity. Reading Wordsworth and Woolf alongside each other should make for an enriched understanding of urban flânerie in British literature, by suggesting how its course was shaped along various ideological and gender fault lines, and also what enduring perplexities beset the writer’s task of engaging with the modern city.